The Cost-Effectiveness of Pulsed-Dye Laser Therapy Among Thai Patients with Facial Port-Wine Stain: A Retrospective Study and Economic Evaluation - Rungsima Wanitphakdeedecha (2022)
Introduction: Port-wine stain (PWS) is a progressive capillary malformation that does not resolve spontaneously without treatment. Pulsed dye laser (PDL) is currently the gold standard treatment for PWS, although it is difficult to attain complete clearance and recurrences are common. This study determined the cost-effectiveness of PDL treatment among Thai patients with facial PWS. Methods: This was a retrospective chart review of 109 Thai patients with facial PWS and treated with PDL at Siriraj Hospital, Thailand from January 2008 to December 2017. The primary outcome of the study was the cost-effectiveness of PDL treatment in the clinical improvement of facial PWS. Results: Ten PDL treatment sessions will have an expected clinical improvement of 60%. At the 10th treatment, the marginal incremental improvement with respect to visit is approximately equal to one. The succeeding treatment sessions will only give an additional improvement of 5–10%. Conclusion: A total of 10 PDL treatment sessions was considered cost-effective as it can achieve 60% clinical improvement among Thai patients with facial PWS.